Feeling 'like you're on … a prison ship' – Understanding the caregiving and attachment narratives of parents of autistic children. Issue 1 (1st February 2021) - Grey, Ben; Dallos, Rudi; Stancer, Rebecca
This study explored the caregiving and attachment relationships of parents of autistic children, analysing 16 Parent Development Interviews conducted as part of a larger project. The interviews were analysed using attachment theory–driven discourse analysis, namely, the Adult Attachment Interview and Meaning of the Child Interview methods of evaluating relational discourse for transformations of meaning with a self-protective function. A multiple case-study approach was used to build an explanatory model of the caregiving and parent–child relationships of the whole sample. The study found a high level of trauma in the parents' early childhood that shaped the way they interpreted their child and the parent–child relationship, often undermining these parents' intentions to form more positive relationships with their own children. An interpersonal understanding of the problems of these families is suggested, seeing difficulties as residing in relationships, maintained by a circular process of ruptures, as parent and child seek to protect themselves from the pain and shame inherent in the experience of 'disconnection', and the apparent failure of the parents' hope for a better relationship with their children than they experienced as children. This may be exacerbated by commonly available autism narratives, which tend to essentialise problems, mechanise parental understanding of their children and encourage parents to experience their child as fundamentally separate, challenging the caregiving system. Clinicians supporting families with autistic children may be assisted by attending to this meaning-making process, seeking creative alternatives to help these parents realise their positive intentions that do not support a shame-based cycle.